A Study of the Location of the Entrance of a Fishway in a Regulated River with CFD and ADCP. (16th May 2012) - Andersson Andersson, Anders G. Anders G.; Lindberg Lindberg, Dan-Erik Dan-Erik; Lindmark Lindmark, Elianne M. Elianne M.; Leonardsson Leonardsson, Kjell Kjell; Andreasson Andreasson, Patrik Patrik; Lundqvist Lundqvist, Hans Hans; Lundström Lundström, T. Staffan T. Staffan
Abstract : Simulation-driven design with computational fluid dynamics has been used to evaluate the flow downstream of a hydropower plant with regards to upstream migrating fish. Field measurements with an Acoustic Doppler Current Profiler were performed, and the measurements were used to validate the simulations. The measurements indicate a more unstable flow than the simulations, and the tailrace jet from the turbines is stronger in the simulations. A fishway entrance was included in the simulations, and the subsequent attraction water was evaluated for two positions and two angles of the entrance at different turbine discharges. Results show that both positions are viable and that a position where the flow from the fishway does not have to compete with the flow from the power plant will generate superior attraction water. Simulations were also performed for further downstream where the flow from the turbines meets the old river bed which is the current fish passage for upstream migrating fish. A modification of the old river bed was made in the model as one scenario to generate better attraction water. This considerably increases the attraction water although it cannot compete with the flow from the tailrace tunnel.